2016
DOI: 10.1016/j.respol.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Additionality or crowding-out? An overall evaluation of public R&D subsidy on private R&D expenditure

Abstract: International audienceThis study analyzes the effect of public R&D subsidies on private R&D expenditure in a sample of French firms during the period 1993–2009. We evaluate whether there is any input additionality of public R&D subsidies by distinguishing between R&D tax credit recipient and non-recipient firms. In addition, combining difference-in-differences with propensity score and exact (both simple and categorical) matching methods, we assess the effect of R&D subsidies between treated (subsidy recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(120 citation statements)
references
References 39 publications
4
88
0
8
Order By: Relevance
“…In line with the results provided by Lokshin and Mohnen [35] or Marino et al [36], we find a strong negative change in the impact of tax credits on R&D investment between the first period (2002)(2003)(2004)(2005) and the second (2006)(2007)(2008)(2009)(2010)(2011). This corroborates the idea that a purely volume-based scheme generates more windfall effects than an incremental scheme.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the results provided by Lokshin and Mohnen [35] or Marino et al [36], we find a strong negative change in the impact of tax credits on R&D investment between the first period (2002)(2003)(2004)(2005) and the second (2006)(2007)(2008)(2009)(2010)(2011). This corroborates the idea that a purely volume-based scheme generates more windfall effects than an incremental scheme.…”
Section: Resultssupporting
confidence: 92%
“…Mohnen [35] or Marino et al [36]. The global neutral effect of tax credits is also explained by the presence of a significant negative indirect effect that counterbalances the positive direct effect.…”
Section: The Efficiency Of the French Policy MIXmentioning
confidence: 98%
See 1 more Smart Citation
“…Em estudo recente com dados da Noruega, Itália e França, Bodas Freitas et al (2017) encontraram efeitos de adicionalidade para as empresas localizadas em setores em que a P&D constitui estratégia predominante de inovação das empresas, sobretudo naqueles baseados em ciência, seguindo a taxonomia de Pavitt (1984). Marino et al (2016) utilizaram dados para uma amostra de empresas francesas entre 1993 e 2009, combinando os métodos de DID com propensity score. Diferenciando-se da maioria das abordagens anteriores, este estudo simulou testes com diferentes dosagens de tratamento a fim de encontrar se há uma quantidade ótima de incentivos que leva à adicionalidade.…”
Section: Revisão Da Literaturaunclassified
“…Leibowicz (2018) found that subsidies improve innovation with stronger spillovers and moderately costly research and development to a great degree. Marino, Lhuillery, Parrotta, and Sala (2016) identified the crowding out effects of public research and development subsidies on private firms. Buchmann and Kaiser (2019) checked German biotech industry and found that subsidy increases the number of patents.…”
Section: Introductionmentioning
confidence: 99%